(untitled) (Journal of Information Systems and Technology Management, 2010)
A quick, effective and powerful alternative for knowledge management is the systematic sharing of best practices. This study identified in the literature recommendations for structuring a best practices database and summarized the benefits of its deployment to the Tribunal Regional Federal da Primeira Região TRF - 1ª Região. A quantitative research was then carried out, with the distribuition of questionnaires to federal judges of the TRF- 1ª Região, which was divided into 4 parts: magistrate profile, flow of knowledge/information, internal environment, organizational facilitator. As a result, we identified the need to have a best practices database in the Institution for the organizational knowledge identification, transfer and sharing. The conclusion presents recommendations for the development of the database and highlights its importance for knowledge management in an organization.